2018
DOI: 10.1177/1403494818761418
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of income on the relationship between body mass index and health-related quality of life in Northern Sweden

Abstract: Income has a role as an effect modifier in the relationship between BMI and HRQoL that can be construed as an indirect income inequality. Efforts to promote HRQoL in populations should consider the different impact of being overweight and obese in different socioeconomic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…In their non-disease-specific sample they found that obese individuals in lower SES group had lower HRQL than those of normal weight in the same SES group, and had lower HRQL compared to those in higher SES groups with the same weight. Subsequent studies confirmed these findings and found both moderator effects [ 60 , 61 ] and mediator effects for obesity/ BMI [ 62 ] regarding the relationship SES and quality of life.…”
Section: Discussionmentioning
confidence: 83%
“…In their non-disease-specific sample they found that obese individuals in lower SES group had lower HRQL than those of normal weight in the same SES group, and had lower HRQL compared to those in higher SES groups with the same weight. Subsequent studies confirmed these findings and found both moderator effects [ 60 , 61 ] and mediator effects for obesity/ BMI [ 62 ] regarding the relationship SES and quality of life.…”
Section: Discussionmentioning
confidence: 83%
“…Obese people may reduce their work quality and productivity in the case of illness. The situation of asking for a leave of absence from production reduces the working time and ultimately lowers work productivity, thus reducing workers’ prospects for employment, working ability, working hours, work efficiency, and quality of work and significantly increases their intention to retire early ( Ramadani et al, 2019 ). The hiring of slim individuals can reduce the risk of productivity loss.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%